Sterols isolated from the soft coral sinularia dissecta - Thao, Nguyen Phuong; Tu, Vu Anh; Thanh, Nguyen Van; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Ho, Kim Young; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, five sterols, gorgost-4-ene-3-one (1), ergost-4-ene-3-one (2), 24-methyleneergost-4-ene-3-one (3), ergost-4-ene-3,6-dione (4), and 24-methylenecholest-4-ene-3,6-dione (5), were isolated from the methanol extract of the soft coral Sinularia dissecta. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. These compounds were isolated from S. dissecta for the first time.